Imagery use in elite youth sport participants: reinforcing the applied significance of achievement goal theory - Harwood, C.; Cumming, J.; Hall, C. (Research Quarterly for Exercise and Sport, 2003)
This study examined the motivational profiles of elite youth athletes to determine whether individual differences in goal orientation corresponded with differential levels of imagery use. Two hundred ninety male (n = 88) and female (n = 202) young athletes (M = 16.6 years, SD = 1.48) completed the Perceptions of Success Questionnaire (POSQ, Roberts, Treasure, & Balague, 1998) to assess dispositional goal orientations and the Sport Imagery Questionnaire (Hall, Mack, Paivio, & Hausenblas, 1998) to assess frequency and function of imagery use. A two-stage cluster analysis on the POSQ scores revealed a three-cluster solution with a multivariate analysis of variance indicating significant differences among cluster groups in imagery use. Athletes in Cluster 3 (higher task/higher ego) used significantly more imagery, regardless of the function than athletes in Cluster 1 (lower task/moderate ego) or Cluster 2 (moderate task/lower ego). These findings are discussed with reference to the role of achievement motivation in influencing young athletes' behavioral investments in mental strategies.